Contribuição ao estudo dendrológico de 5 Parkias (Leguminosae) da Amazônia - Loureiro, Arthur Araújo; Silva, Marlene Freitas da (Acta Amazonica, 1972)
In this paper a contribution to the dendrological knowledge of the amazonian species of the genus Parkia (Leguminosae) in given by the authors, by including the botanical description, geographical distribution, habitat and anatomical description of the woods of the following species : P. pendula, P. decussata, P. oppositifolia, P. gigantocarpa and P. multijuga. a table showing the main differential structures of their woods is also presented, including 15 photos.